Vulnerability of WAMZ member countries to external shocks: Implications on the convergence process - Olorunsola E. Olowofeso; Maimuna John-Sowe; Ibrahima Diallo; Dauda Mohammed; Hissan Abubakari; Eric Sambolah; Kayode Ezekiel Adedeji (West African Monetary Institute (WAMI), 2022)
The economic integration process requires appropriate understanding of the degree of vulnerability of member states to various kinds of shocks as well as identification of appropriate measures to mitigate the impact of these shocks on macroeconomic performance. Consequently, this study seeks to measure the degree of vulnerability of WAMZ member countries to external shocks by computing economic vulnerability indices (EVI) for each member state and the zone as a whole, utilizing data spanning over the period 2004 - 2019. The study adopted a modified version of Briguglio (2014) methods to compute the EVI for the WAMZ countries by utilizing three of the four components - trade openness, exports concentration, and dependence on strategy imports. The EVI3 was chosen as the preferred index for its robustness, as it uses statistical methodology in generating the component weights. The computed EVI values and the component indices ranged between 0 and 1, with a high score in the index corresponding to a high level of vulnerability and vice- versa. Results from the empirical analysis show that Liberia is the most open economy, followed by Ghana and Guinea, while Nigeria and The Gambia are the least open. On the other hand, export concentration is highest in Nigeria, followed by Liberia and Sierra Leone, and lowest in The Gambia, while dependence on strategic imports is highest in The Gambia and lowest in Ghana and Nigeria. The average EVI for the Zone is 0.57 point, implying that the Zone, as a whole, is vulnerable to external shocks (particularly to commodity prices such as iron ore, bauxite, gold, etc.) Specifically, Liberia, Ghana and Sierra Leone were found to be most vulnerable in the Zone, while The Gambia showed the least vulnerability to external shocks. Macroeconomic vulnerability could be mitigated in the WAMZ economies by implementing a number of measures aimed at building economic such as ensuring macroeconomic stability with a healthy fiscal position and diversifying their output and export base; promote savings and create stabilization funds both of which could come handy in periods of commodity price falls. They could also explore using market-based instruments such as forwards, futures, and options to manage commodity price risks.
Keywords: C38; C43; O13; 330; Commodity dependence; external shocks; vulnerability index; macroeconomic convergence